Circulating Tumor Cells Expressing the Prostate Specific Membrane Antigen (PSMA) Indicate Worse Outcome in Primary, Non-Metastatic Triple-Negative Breast Cancer - Kasimir-Bauer, Sabine; Keup, Corinna; Hoffmann, Oliver; Hauch, Siegfried; Kimmig, Rainer; Bittner, Ann-Kathrin (Frontiers in Oncology, 2020)
Background: We analyzed mRNA profiles of prostate cancer related genes in circulating tumor cells (CTCs) of primary, non-metastatic triple-negative breast cancer (TNBC) patients (pts) before and after neoadjuvant chemotherapy to elucidate the potential of prostate cancer targets in this BC subgroup. Method: Blood from 41 TNBC pts (n=41 before / 26 after therapy) was analyzed for CTCs applying the AdnaTest EMT-2/Stem Cell Select. Multimarker RT-qPCR allowed the detection of the prostate specific antigen PSA, the prostate specific membrane antigen PSMA, full-length androgen receptor (AR-FL) and AR splice-variant seven (AR-V7). Results: Before therapy, at least one prostate cancer related gene was detected in 15/41 pts (37%). Notably, in 73% of AR-FL positive cases, AR-V7 was co-expressed. After therapy, CTCs of only one patient harbored prostate cancer related genes. AR-V7+ and PSMA+ CTCs significantly correlated with early relapse (p=0.041; p=0.00039) whereas PSMA+ CTCs also associated with a reduced OS (p=0.0059). This correlation was confirmed for PSMA+ CTCs in univariate (PFS p=0.002; OS p=0.015), but not multivariate analysis. Conclusion: Although CTCs that expressed prostate cancer related genes were eliminated by the given therapy, PSMA+ CTCs significantly identified pts at high risk for relapse. Furthermore, AR inhibition, often discussed for this BC subgroup, might not be successful in the primary setting of the disease since we identified AR-FL+ CTCs together with AR-V7+ CTCs, associated with therapeutic failure.